1994
DOI: 10.1007/bf00194480
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to specific molecules of the retina in proliferative vitreoretinal disorders

Abstract: In recent years, several reports have contributed to a growing suspicion that there is immunologic involvement in proliferative intraocular disorders such as proliferative vitreoretinopathy and proliferative diabetic retinopathy. Immune privilege, as in the brain, ovary and testis, also exists in the eye. Therefore, immune responses to unique molecules of the eye, e.g. retinal S-antigen (S-Ag), which the immune system never learns to regard as "self", are possible. This study describes the presence of S-Ag, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
6
1
1
Order By: Relevance
“…Such inflamed eyes usually behave like a culture media and produce cytokines that may immunologically activate released RPE and other responsible cells to trigger PVR cascade. 37 In the current study, we did not observe any association of age, gender, presence of retinitis, choroiditis, and retinal vasculitis as well as etiology on the study outcomes, which could be due to small sample size.…”
Section: Discussioncontrasting
confidence: 69%
“…Such inflamed eyes usually behave like a culture media and produce cytokines that may immunologically activate released RPE and other responsible cells to trigger PVR cascade. 37 In the current study, we did not observe any association of age, gender, presence of retinitis, choroiditis, and retinal vasculitis as well as etiology on the study outcomes, which could be due to small sample size.…”
Section: Discussioncontrasting
confidence: 69%
“…In comparison, a diverse range of different probe sets were upregulated in ocular MVEC that included genes involved in immune responses, signal transduction and the cellular responses to stimuli. Immune mechanisms are thought, in part, to be important in the pathogenesis of both diabetic retinopathy14 15 and wet AMD 16 17. Given that the microvasculature undergoes regular remodelling and is the site of both physiological and pathological angiogenesis, it is not surprising that a number of genes involved in cell signalling and cell basement membrane turnover are also differentially upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that the increased levels of soluble adhesion molecules play an important role in macrovascular [6][7][8] as well as in microvascular complications of diabetes [4,5,8]. Besides autoimmunological mechanisms, additional immune interactions may also be involved in the pathogenesis of microvascular complications in diabetes mellitus type 1 [9]. Diabetic retinal neovascularization is considered to be a consequence of retinal ischaemia caused by capillary occlusion.…”
mentioning
confidence: 99%